Air Pollution and Tourism: Evidence from G20 Countries. (February 2022) - Churchill, Sefa Awaworyi; Pan, Lei; Paramati, Sudharshan Reddy
Theoretically, it is well argued that environmental factors affect the growth of the tourism industry; however, from an empirical perspective, some gaps still exist in the literature. We empirically examine the effect of carbon dioxide (CO2 ) and particulate matter (PM2.5) emissions on tourist arrivals in a panel of G20 countries. Using annual data from 1995 to 2014 and a series of panel data models, our results suggest that the growth of both CO2 and PM2.5 emissions adversely affects international tourist arrivals. The results also show that the observed effect of CO2 emissions is more pronounced in developed economies, while the effect of PM2.5 emissions is stronger for developing economies. Given these findings, our study provides and discusses a number of policy and practical implications.